Evaluation of clinical findings in patients with lichen planus: A retrospective study - Esen, Mustafa (My University, 2023)
Aim: Lichen planus is a papulosquamous disease that affects skin and mucous membranes. In this study, we aimed to evaluate the clinical and demographic characteristics, treatment models, and accompanying comorbidities of patients with lichen planus. Materials and Methods: Our study included 202 patients who were diagnosed with LP clinically and histopathologically between May 2018 and May 2023. Patients’ age, gender, involvement features, additional systemic diseases, laboratory findings and applied treatments were recorded retrospectively. Results: Of the 202 patients in our study, 116 (57.4%) were female and 86 (42.6%) were male. The average age of the patients was 46.42 years (13-84). The average duration of the disease was 10.40 months (1-196). The classic type (120 patients, 64.9%) was observed most typically in skin involvement, while reticular pattern (60 patients, 85.7%) was observed in oral involvement. Skin involvement was detected in 185 (91.6%), oral mucosa involvement in 70 (34.7%), genital involvement in 16 (7.9%), scalp involvement in 30 (14.8%), inverse involvement in 20 (9.9%), palmoplantar involvement in 5 (2.5%) and nail involvement in 21 (10.4%) of the patients, while no ocular involvement was detected. Anti-HCV positivity was found in two (1%) patients. HBsAg positivity was detected in 11 (5.4%) patients. While the most frequent accompanying comorbidity was hypertension with %20.3 (n:41), depression-anxiety was the sequent with 14.4% (n:29). While 154 (76.2%) of the patients received only topical treatment, it was seen that 5 (2.5%) patients were given only systemic treatment. In comparison of the age groups 18-45 and >45, the ratio of DM, hyperlipidemia and hypertension was identified significantly high in the group >45. Conclusion: Our study shows many similarities with the literature data. However, we believe that prospective cohort studies including more patients are needed to understand LP, whose clinical and epidemiology has not been sufficiently elucidated.
Keywords: Oral mucosa; Nail; Lichen planus